(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s ((3eOQSI LGeY GdYJjbs)
(3ChdgG (B:s
(3Ye jJSGAdhf CUdg(B: (3Yf eG aMPa deG eQ heYfi gPG GdGSJagGe JaNje TCf eG jSCdhf Yfgs
(3BNQgG (B:s
(3hajg JYSa EdG Cf jQGO Hg GdfGS cbhdg(B: (3jhe jOY GdOGY acGfeG bQC GdcJH GdJj CfRdgG Gddg JYGdi cdgGs
(3JHUQI GdYfhGf (B:s
(3JaSjQ GdHjVGhjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4/109s
(3cTa GdXfhf (B1/186s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs